THE RELATIONSHIP BETWEEN FAMILY COMMUNICATION PATTERN AND YOUTH SELFCONCEPT IN RURAL MALAYSIA (Jurnal Pembangunan Sosial, 2023)
This study aimed to investigate the relationship between family communication patterns and self-concept among youth in rural areas.The sample consisted of 315 participants (150 boys and 165 girls), selected using a simple random sampling technique. The RevisedFamily Communication Pattern (RFCP) Survey, which has two dimensions - conversational orientation and conformity orientation,was used to measure the relationship between the variables. The Tennessee Self-Concept Scale, which has six dimensions - social,moral, family, ethical, physical, and personal - was also used. Demographic factors such as gender, race, education, and religiousaffiliation were measured. The results showed significant relationships between family communication patterns for conversational orientation and physical, ethical, personal, family, and social self-concept, with the exception of moral self-concept, which showed medium levels. Additionally, there were significant relationships between conformity orientation and moral and ethical self-concept, and weak relationships with physical, family, and social self-concept. These findings reaffirm the importance of family communication patterns in shaping the selfconcept of youth in rural areas.